Workplace Bullying and Psychological Distress in Public Institutions in Ghana - Darko, George; Björkqvist, Kaj; Österman, Karin (European Journal of Social Science Education and Research, 2024)
Sex differences and psychological distress associated with workplace bullying were investigated in a total of 1,273 employees in three public institutions in Ghana. The effect of level of occupation (junior vs. senior) was also explored. Victimisation from bullying was measured with an abbreviated version of the Work Harassment Scale (WHS-7), and mental health associations with workplace bullying were assessed with an indicator of psychological distress (General Health Questionnaire, GHQ-12). 19.1 percent of the respondents had been bullied “often” or “very often”. There were no sex differences in frequency of victimisation from bullying. Occupational status was significantly associated with bullying: junior staff members reported higher levels of victimisation from bullying and higher levels of psychological distress than senior staff members. Workplace bullying appears to b common in public institutions in Ghana, and has significant negative outcomes for individuals, especially junior staff members. The findings have implications for policy-makers, employers, and employees.